Development trends and the association of stakeholders in tourism development process in the case of Pärnu County (Estonia) - Heli Müristaja (European Regional Science Association (ERSA), 2003)
In the last years almost every state, region or city in the world, included Estonia, has taken the goal to increase the portion of tourism economy in the total economy. The reason is that they see in tourism a possible development key to the economic growth. Tourism is a total sum of phenomena and relations which arise from interrelation processes between tourists, suppliers, hosting governments and communities to attract and host tourist and other visitors. The national tourism development plan of Estonia for the years 2002-2005 defines that due to the geographical position, natural and climatic conditions, sights, attractions, resources and cultural traditions the main competitors of Estonia are Scotland, Wales, Ireland, rural parts of England, Sweden, Denmark, Finland, Poland, Latvia and Lithuania. The basis of tourism experience of all these destinations is historical sights and architectural heritage, the cultural life based on traditions and pure and diversified nature, but there are no world-famous attractions. The significance of tourism in Estonian economy has continually been increasing in the last 10 years, having direct impact of 10% and indirect impact of 15% to GDP. The importance of employment and the share of Estonian export of goods and services provide about 16%. In the year 2002 there was 3.25 million international visitors in Estonia and the income form tourism increased 3-4%, reached 12 billion Estonian kroons. Western Estonia, where Pärnu County is situated, is the lowest and the most marine region, covering the coast of the Gulf of Riga. The coastal area is mostly low, stony, sandy or overgrows with reed here and there. The most important push factor in tourism demand is Pärnu city, having an over 160-years history as a resort. The visitors surveys in the last couple years are showing that the visitors of Pärnu city are a little bit tired of the static destination and they are pleased to broaden their travel experiences. The finest possibility would be to widen the tourism product to the county where there is a lot of unused tourism potential - cultural and natural attractions, interesting people and beautiful scenery. The main purpose of my article is to analyse potential development trends and the association of stakeholders in development process: their benefits and responsibilities, the flows of money and information
Keywords: 330